Complete mitochondrial genome sequences of rare haplotype E4 from Phu Quoc ridgeback dog - Dũng, Trần Hoàng; Mai, Trương Nguyễn Thị Như; Công, Nguyễn Thành; Hiếu, Huỳnh Văn (Vietnam Journal of Biotechnology, 2018)
Phu Quoc ridgeback dog is an invaluable species in Vietnam. The discovery of high-frequency rare halophytes E4 and E1 in Phu Quoc ridgeback dog while evaluate analyzing its genetic distances is an unexpected event. In this research, the primer-walking strategy was used to sequence the whole mtDNA of Phu Quoc ridgeback dogs carrying E4, B1 and E1 halophytes to explore trace of Phu Quoc ridgeback dog’s origin. These mtDNA’s length (16,760 bp for PQ1 and 16,731 for PQ2) fall into the range of 16.7 kb, particularly, 16.760 bp in E4 dogs and 16.731 bp in B1 dogs and is basically similar to the ones of other dog breeds. The difference in length between E4 and B1 haplotype is mainly due to the difference of motif repeat frequency in the control region. The number of genes, starting and ending codes of E4’s mtDNA are similar to other common halophytes. Genetic distances between Phu Quoc ridgeback dogs’ E1, E4 haplotypes and Pungsan dogs (EU789662) in the same clade in the phylogenetic tree are 0,072% and 0,24%, respectively, showing that Phu Quoc dogs with E haplotypes are very close relatively to Pungsan dogs in North-Korea. Although belonging to the same haplogroup, the genetic distance between Phu Quoc dogs E1 and E4 haplotype is 0,23%. In the other hand, genetic distances between E1, E4 haplotypes Phu Quoc ridgeback dogs and the closest grey wolves on phylogenetic tree are 0,3% and 0,1%, respectively. This is the first mitochondrial genome of E4 haplotype dogs to be sequenced and analyzed.